Multicompartmental analysis of POPs and PAHs in Concepciόn Bay, central Chile: Part II – Air-sea exchange during Austral summer. (April 2022) - Pozo, Karla; Gómez, Victoria; Tucca, Felipe; Galbán-Malagón, Cristóbal; Ahumada, Ramón; Rudolph, Anny; Klánová, Jana; Lammel, Gerhard
Abstract: Air-sea exchange of POPs and PAHs was assessed in Concepción Bay during January, summer 2015. Results showed low levels, in air and water, for POPs (1–20 pg m −3, and 6–50 pg L −1, respectively) and for ΣPAHs (1–2 ng m −3 and 1–2 ng L −1, respectively). The highest levels were found for PBDEs (200–20, 000 pg L −1 ) in the water samples (3-fold times higher than PCBs and OCP) and PBDE209 accounted for 90% of total ΣPBDEs. Air–sea exchange fluxes (ng m −2  d −1 ) were low in general, with exception of PBDEs showing values up to 40, 000 ng m −2  d −1 . Net deposition was found for PAHs, HCB and some PBDEs; while, BDE99, and BDE100 showed net volatilization. These findings contribute with new data of diffusive air-sea exchange on the southern hemisphere Pacific coast. Graphical abstract: Unlabelled Image Highlights: POPs levels were low in Concepción Bay in air and water samples with exception of PBDEs and PAHs. PBDE-209 showed the highest levels in water (with 90% of prevalence). Air-sea exchange recorded volatilization and deposition patterns. Upwelling, in Austral summer, may enhance the air-sea exchange of chemicals.